2012
DOI: 10.1002/met.1320
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the East Asian Monsoon: a review

Abstract: ABSTRACT:This study presents reviews of recent research on the structure and the multiscale variability in the East Asian monsoon. The boreal summer and winter seasons in the East Asian monsoon region exhibit significant intraseasonal, interannual and interdecadal variabilities. The interannual intensity of the East Asian summer monsoon (EASM) is mainly associated with the position of the centre of the Bonin High, which may be distinguished from the North Pacific anticyclone. The frequencies of heavy rainfall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 61 publications
3
75
0
Order By: Relevance
“…We computed the daily PET and PET /P and then estimated their annual mean values at individual weather sites. Due to the decadal variation in eastern Asian monsoon circulation (Ding et al, 2008;Ha et al, 2012), the entire analysis period is divided into two subperiods (1961-1983 and 1984-2010) by applying three change-point methods to the temporal variations in PET /P (Pettitt, 1980;Lund and Reeves, 2002;Beaulieu et al, 2012, see Sect. S2 of Supplement for details).…”
Section: Methods and Datamentioning
confidence: 99%
“…We computed the daily PET and PET /P and then estimated their annual mean values at individual weather sites. Due to the decadal variation in eastern Asian monsoon circulation (Ding et al, 2008;Ha et al, 2012), the entire analysis period is divided into two subperiods (1961-1983 and 1984-2010) by applying three change-point methods to the temporal variations in PET /P (Pettitt, 1980;Lund and Reeves, 2002;Beaulieu et al, 2012, see Sect. S2 of Supplement for details).…”
Section: Methods and Datamentioning
confidence: 99%
“…In fact, such conditions have resulted in relatively frequent floods and droughts in South Korea [32,34]. The severity of floods and droughts is highly variable, as the EASM exhibits a substantial interannual variability in intensity [35]. Eighteen droughts have occurred over the last 100 years, with severe droughts occurring in seven-year cycles since 1994 (Table 1).…”
Section: Major Challenges In the Water Sectormentioning
confidence: 99%
“…The observed changes are predicted to intensify until at least 2100, along with an increase in the occurrence and severity of In recent decades, changes in the climate of South Korea have been observed, namely an above-global-average increase in surface temperature, and a substantial increase in the frequency and intensity of heavy rainfall events [36][37][38]. From 1954 to 1999, surface temperature increased at a rate of 0.23 • C per decade, and from 2001 to 2010, at a rate of 0.5 • C per decade [35]. Choi et al (2008) [39] reported that, in the region of the Lake Soyang watershed, the precipitation of extremely wet days increased by 61 to 80 mm per decade over the period from 1973 to 2007.…”
Section: Major Challenges In the Water Sectormentioning
confidence: 99%
“…One has a period of 30-90 days, and is often referred to as the intraseasonal oscillation (ISO); the other has a period of 10-20 days, and is often referred to as the quasi-biweekly oscillation (QBWO) [4][5][6][7]. The studies on both the mechanism and the climatic impacts of the ISO and QBWO have been hot topics since the early 1970s [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%